Do Ecological Factors Determine Nationwide Performance of Supply Chain? Evidence from Thailand - Wasesa, Supa; Syah, Amirul (ExcelingTech, 2020)
Present study aims to investigate the impact of ecological factors; GDP growth rate (GGR), degree of openness (DOO), exchange rate (EXR) and balance of payment (BOP) on foreign direct investment (FDI). Study also examines the effect of FDI on the performance of nationwide supply chain (NSCP). Moreover, study examines mediating role of FDI on the relationship between GGR, DOO, EXR and BOP. For this purpose, study utilized the data of 123 ecologists of Thailand through an online questionnaire. Study applies structural equational modeling (SEM) for examining the empirical results. Study tests the reliability and validity of the data with the help of measurement model while structural model is used for testing the hypothesis. Results of the study show positive impact of DOO, GRR, EXR and BOP on FDI. Results further show significant and positive relationship between FDI and NSCP. Findings reveal that FDI significantly mediates the relationship between GGR, DOO, BOP and NSCB. While the relationship between EXR and NSCB is not mediated by FDI. Study suggested that companies have to start different investment programs for attracting the foreigners so that they can invest their money in the company.